please let me know the answer of this question
Attachments:
![](https://hi-static.z-dn.net/files/d42/9fc4ab975dd6d22fc3c392c70beb8ad7.jpg)
Answers
Answered by
0
Answer:
I got only half answer another portion I didn't got that
Attachments:
![](https://hi-static.z-dn.net/files/d34/d6238d6850828407d3fae42ff20ed1df.jpg)
Answered by
15
Answer:
d)
Step-by-step explanation:
3x + 6y = 9
3x = 9 - 6y
–––(1)
Putting (1) into the 2nd equation,
7x - 15y = 2
63 - 42y - 45y = 2 × 3
63 - 87y = 6
- 87y = 6 - 63
- 87y = 57
–––(2)
Putting (2) into (1),
The point of intersection of lines is
Similar questions